2006
DOI: 10.1111/j.1574-0862.2006.00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Off‐farm labor supply responses to permanent and transitory farm income

Abstract: A sample of Iowa farm couples is used to evaluate whether off-farm labor supply decisions respond to permanent and transitory components of farm income. Off-farm labor supply of both spouses declines in response to increases in permanent farm income. Farm wives also reduce off-farm labor supply in response to positive transitory farm income shocks. Consequently, one mechanism farm households use to smooth their goods consumption when facing fluctuating farm income is to modify their consumption of leisure. Abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
3
14
0
1
Order By: Relevance
“…This is in line with findings from Ahearn et al (2006) and Kwon et al (2006) that the supply of off-farm labour decreases when government subsidies increase. This confirms the suggestion of Douarin et al (2007) that accounting for the extent of off-farm opportunities is important in analyses of the impacts of CAP reforms, since these may lead to a reallocation of labour.…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with findings from Ahearn et al (2006) and Kwon et al (2006) that the supply of off-farm labour decreases when government subsidies increase. This confirms the suggestion of Douarin et al (2007) that accounting for the extent of off-farm opportunities is important in analyses of the impacts of CAP reforms, since these may lead to a reallocation of labour.…”
Section: Discussionsupporting
confidence: 91%
“…The basic idea is that rainfall variability would introduce exogenous income shocks, and since households can use savings to smooth consumption, transitory income shocks may not directly affect consumption. 6 Further, as Kwon et al, 2006 points out, a temporary shock to farm income can be caused by variability in weather. Transitory shocks have an impact on current period farm income.…”
Section: Model Specificationmentioning
confidence: 99%
“…Transitory shocks have an impact on current period farm income. Therefore, one can assume the coefficient of variability in rainfall 7 (RAIN_CV) can be used to measure the transitory component associated with farm household income 8 (Kwon et al, 2006).…”
Section: Model Specificationmentioning
confidence: 99%
“…Becker (1981) indicated the trend in the past several decades that increasing job opportunities and rising wages for women have significantly increased women's participation in the paid labor markets. In an interesting empirical study, Findeis (2002) Kwon, Orazem, and Otto (2006) found that for an unforeseen adverse shock to the farm operations, farmers' wives are more likely to join off-farm labor market. Farm husbands were less sensitive to transitory farm income changes, thus less likely to switch to off-farm labor market.…”
Section: Changes In Off-farm Wage ( O W )mentioning
confidence: 99%